2006
DOI: 10.1139/p06-052
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of a viscous-fingering instability in a fluid with a temperature-dependent viscosity

Abstract: We have performed numerical simulations of the flow of hot glycerine as it displaces colder, more viscous glycerine in a radial Hele–Shaw cell. We find that fingering occurs for sufficiently high inlet velocities and viscosity ratios. The wavelength of the instability is independent of inlet velocity and viscosity ratio, but depends weakly on cell width. The growth rate of the fingers is found to increase with inlet velocity and decrease with the cell width. We compare our results with those from experiments.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Numerical studies of various miscible displacements regimes agree qualitatively with the stability analyses above [2,18,19,20,21]. In general, at the late stages of interfacial growth, they find that at sufficiently low values of thermal lag, or if the thermal regime is highly diffusive, the evolution depends entirely on the solutal viscosity ratio.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Numerical studies of various miscible displacements regimes agree qualitatively with the stability analyses above [2,18,19,20,21]. In general, at the late stages of interfacial growth, they find that at sufficiently low values of thermal lag, or if the thermal regime is highly diffusive, the evolution depends entirely on the solutal viscosity ratio.…”
Section: Introductionsupporting
confidence: 68%
“…Here, we summarise the solution procedure to evaluate the transient temperature field and quasi-static pressure in order to reconstruct the interface velocity with equation (21).…”
Section: Methodsmentioning
confidence: 99%
“…Sheorey and Muralidhar [5] performed a numerical simulation of the displacement of oil by hot water in porous media and found that the displacement patterns change according to the non-isothermal fields which results in higher oil recovery compared to isothermal cases. Holloway and de Bruyn [6,7] experimentally and numerically studied the viscous fingering that occurs when hot glycerin displaces cooler, more-viscous glycerin in a radial HeleShaw cell. They showed that fingering occurred for sufficiently large temperature difference between the injected and the displaced liquid and for sufficiently high flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, interest in the control of the properties of this instability by mechanical, [1][2][3][4][5][6][7] thermal, [8][9][10][11][12][13] or chemical [14][15][16][17][18][19][20][21][22][23][24] ways for instance are of constant interest in the literature. Numerous experimental and theoretical works have already shown that the properties of the fingers (such as their mixing length or their area) can be strongly affected by in situ changes in the viscosity field distribution induced by gradients of temperature or composition in the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Riolfo et al have furthermore evidenced that a reaction can even trigger fingering when a viscous polymer solution displaces a less viscous reactive solution. 22 Qualitative understanding of the thermally-or chemically-driven control of fingering properties typically rely on numerical computation of the spatio-temporal evolution of the temperature 9,12 or concentrations 18,21,22 fields. The viscosity field is then deduced on the basis of a state equation relating the viscosity to temperature or chemical concentrations.…”
Section: Introductionmentioning
confidence: 99%